2001
DOI: 10.1159/000051699
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic Liaison Service in Dermatology

Abstract: Background: Empirical investigations examining the psychosocial distress and need for care of dermatology patients are rare. Little is known about the use of psychotherapeutic interventions in routine care. Objective: To evaluate the psychosocial distress of dermatological inpatients, the need for psychotherapeutic interventions and their realization in the framework of a psychosomatic liaison service. Methods: 86 patients from one unit at the University Dermatology Clinic in Freiburg underwent psychodiagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…In several studies, psychiatric disorders were reported to be observed more in people with dermatological diseases (23)(24)(25)(26)(27)(28). In a study done in cases with vitiligo, 40% of cases were found to be depressive and had low self-esteem (29).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, psychiatric disorders were reported to be observed more in people with dermatological diseases (23)(24)(25)(26)(27)(28). In a study done in cases with vitiligo, 40% of cases were found to be depressive and had low self-esteem (29).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the interpretation of physiological, pharmacological and psychological studies of autonomic abnormalities in AD is rendered difficult by the complexity of mechanisms that maintain homeostasis, and further studies on isolated aspects of the disease will be needed to clarify its pathogenesis. Nevertheless, AD patients seem to have a higher activation level, physiologically as well as psychologically, further emphasizing that the use of psychotherapeutic intervention [40], even in disease-free intervals, in addition to the necessary dermatological treatment may be beneficial. …”
Section: Discussionmentioning
confidence: 99%
“…Data from the literature have shown that 51% of patients with dermatological problems require psychotherapeutic treatment, 28% have been willing to have psychotherapy and 38% of them have received psychiatric help. Liaison services do provide assistance for patients who have psychiatric problems that relate to skin disorders [ 23 ]. In a survey study, 23.2% of medical managers provide psychosomatic treatment in addition to dermatological care and treatment.…”
Section: Discussionmentioning
confidence: 99%